Using Factor Mixture Models to Evaluate the Type A/B Classification of Alcohol Use Disorders in a Heterogeneous Treatment Sample. (30th March 2017) - Hildebrandt, Tom; Epstein, Elizabeth E.; Sysko, Robyn; Bux, Donald A.
Abstract : Background: The type A/B classification model for alcohol use disorders (AUDs) has received considerable empirical support. However, few studies examine the underlying latent structure of this subtyping model, which has been challenged as a dichotomization of a single drinking severity dimension. Type B, relative to type A, alcoholics represent those with early age of onset, greater familial risk, and worse outcomes from alcohol use. Methods: We examined the latent structure of the type A/B model using categorical, dimensional, and factor mixture models in a mixed‐gender community treatment‐seeking sample of adults with an AUD. Results: Factor analytic models identified 2 factors (drinking severity/externalizing psychopathology and internalizing psychopathology) underlying the type A/B indicators. A factor mixture model with 2 dimensions and 3 classes emerged as the best overall fitting model. The classes reflected a type A class and 2 type B classes (B1 and B2) that differed on the respective level of drinking severity/externalizing pathology and internalizing pathology. Type B1 had a greater prevalence of women and more internalizing pathology and B2 had a greater prevalence of men and more drinking severity/externalizing pathology. The 2‐factor, 3‐class model also exhibited predictive validity by explaining significant variance in 12‐month drinking and drug use outcomes. Conclusions: The model identified in this study may provide a basis for examining different sources of heterogeneity in the course and outcome of AUDs.